Psychology applied to teaching - Biehler, Robert F. 1927- (Houghton Mifflin, 1997)
Applying psychology to teaching. Stage theories of development. Age-level characteristics. Understanding cultural diversity. Dealing with student variability. Devising and using objecttives...